The use of GIS application in identifying youth recreational area in Subang Jaya, Selangor - Zainol, R.; Maidin, S.L. (2011)
The paper presents the use of GIS application in identifying the youth recreational area in Subang Jaya, Selangor. The main objective of this paper is to identify existing youth recreational area, its thresholds and amenities in Subang Jaya. Method used in this study is divided into two main parts. First is by using GIS application, all related recreational area, its thresholds and amenities are identified spatially. Then spatial analysis is carried out to match with the youth population in this township. In addition, the output is also matched against the government policies of providing such recreational area. Findings show that youth recreational area is not limited to outdoor area but also indoor area too. This is consistent with the high demand of land area development in urban areas. However, findings also show the difference between the government policies and plans against what is actually been implemented. It is also found that many recreational area is not easily accessible to the youth. As an example, there is a need for a safe bicycle lane/pedestraian walkway in connecting housing areas with schools and urban parks and public amenities. Furthermore, it is also found that the public amenities lack of police beat stations or neighbourhood patrols to ensure safety. In summary, the stakeholders of Subang Jaya should look into mechanism of turning the existing recreational area into more sustainable youth recreational area.